Етнографічні дослідженнякримськотатарського житла - Акчуріна-Муфтієва, Н. (Народна творчість та етнографія, 2005)
Crimean decorative ethnographical art as a unique culture is the topic for discussion in this article. The architectural particularities of the buildings in Crimea-Tatar villages and the history of their study have been described very detailed. The interior design of the village houses of Crimea-Tatars takes a considerable place in the article. The contemporary building in Crimea accordingly to the author has tendency to lean toward the traditional style in order to overcome the depressive contemporary urban style.